Farmer willingness to pay for seed-related information: Rice varieties in Nigeria and Benin - Horna, Daniela; Smale, Melinda; von Oppen, Matthias (Cambridge University Press, 2007)
This study examines farmers’ preferences for seed of new rice varieties (improved and NERICA) and their willingness to pay (WTP) for information embodied in the seed, in villages of Nigeria and Benin. Information might not generate rivalry among its users but excludability is certainly a characteristic of information and its delivery can generate incentives for private participation. Conjoint utility analysis is used to estimate the structure of farmers’ preferences for rice seed. Farmers prefer one variety based on the utility they obtain from its attributes, which depends on their own social and economic characteristics. Contingent methods are used to elicit preferences and rice seed price. The marginal values of attributes are estimated with an ordered probit regression. The WTP for seed-related information is derived from the utility model. The results have implications for the best way to finance extension services in the areas of intervention, particularly for new rice varieties.